Modeling approaches for reducing the carbon footprint of forest industry enterprises - Medvedev Sergey; Yakusheva Maria; Zyryanov Mikhail (E3S Web of Conferences, 2024)
This paper presents the results of a study of individual aspects of reducing the carbon footprint from the activities of forest industry enterprises. This issue is one of the most relevant in modern science and practice. The existing conflict between production and the environment requires adequate solutions and due attention from all stakeholders. The goal of the work was realized through identifying the most significant areas of carbon footprint formation and assessing opportunities to reduce such impact. The main method of work is analytical. As a result of the study, a model of the environment of an industrial enterprise was formed, including factors and variables of the external and internal environment. The rationale for the relevance of reducing the carbon footprint of industrial enterprises is given. A schematic diagram of the stages of formation of a carbon footprint from the activities of a timber processing enterprise has also been developed. The result of the study is the identification of the most significant areas of carbon footprint formation from the activities of forest industry enterprises, as well as the identification of opportunities to reduce such impact.